Nur Izzaty, UMPSA A.D.A.B Student Figure Innovation and Entrepreneurship Leaders for Sustainable Development Goals - Nor Azlina, Ahmad (UMPSA, 2024)
KUANTAN, 18 May 2024 – The Mercu Sanjung Award (MARS) Ceremony, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) which took place at Zenith Hotel, Kuantan recently saw an outstanding student from the Faculty of Computing, Nur Izzaty Ariffin, awarded as an A.D.A.B Student Figure.